Fracasso Escolar e o fen??meno da Medicaliza????o: um estudo sobre as concep????es dos professores - Sperandio, Maria de Lourdes (2014)
This study aimed to analyze teachers??? concept about school failure and its relation with medicalization on education. Theoretical and empirical studies have been conducted. As methodological approach was used qualitative research and was defined as theoretical framework to sustain and discuss the data collected with the interviews the concepts of Foucault's disciplinary society, control and power; and to understand the educational institutions was used the theory of social reproduction and concepts of symbolic violence, habitus and cultural capital discussed by Bourdieu. The research subjects were active teachers in public schools in first elementary level of the city of Londrina, Parana state, Brazil. In the first empirical study were realized 11 semi-structured interviews and in the second, three in-depth interviews were conducted. Data collected from the interviews were analyzed using the technique of content analysis proposed by Bardin. As result, the research allowed to know what the teachers think about school failure and medicalization on education, and the teachers??? concern to get out of school the solution to the academic performance of students, mainly in specialized clinics and family. It was concluded that teachers are not prepared to meet the challenges of a school formed by a diverse clientele in values and interests. Meanwhile, medicalization has been the resource that teachers use to maintain control and order in the school.